2002
DOI: 10.1021/ja0200948
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Phosphate Monoester Monoanions in Aqueous Solution. 1. Quantum Mechanical Calculations Support the Existence of “Anionic Zwitterion” MeO+(H)PO32- as a Key Intermediate in the Dissociative Hydrolysis of the Methyl Phosphate Anion1

Abstract: The dissociative hydrolysis reaction of the methyl phosphate monoanion has been studied for the reactant species CH(3)OPO(3)H(-) (1) and CH(3)OPO(3)H(-) x H(2)O (1a) in the gas and aqueous phases by density functional theory (B3LYP) calculations. Nonspecific solvation effects were taken into account with the polarizable continuum model PCM either by solvating the gas-phase reaction paths or by performing geometry searches directly in the presence of the solvation correction. In agreement with previous theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
84
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(104 citation statements)
references
References 33 publications
20
84
0
Order By: Relevance
“…The dissociative mechanism, which proceeds via a six-membered-ring transition state involving the water molecule, is found to be favored more than the associative mechanism, in both the gas and solution phase. In agreement with previous theoretical results, [8] DFT calculations carried out using the hybrid functional B3 LYP on the dissociative hydrolysis reaction of CH 3 OPO 3 H À indicated that, in the gas phase, proton transfer to the methoxy group is concerted with PÀO cleavage. The dissociative pathway of the CH 3 Keywords: ab initio calculations · cluster compounds · diphosphate anions · gas-phase chemistry · mass spectrometry · phosphorus transition state.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…The dissociative mechanism, which proceeds via a six-membered-ring transition state involving the water molecule, is found to be favored more than the associative mechanism, in both the gas and solution phase. In agreement with previous theoretical results, [8] DFT calculations carried out using the hybrid functional B3 LYP on the dissociative hydrolysis reaction of CH 3 OPO 3 H À indicated that, in the gas phase, proton transfer to the methoxy group is concerted with PÀO cleavage. The dissociative pathway of the CH 3 Keywords: ab initio calculations · cluster compounds · diphosphate anions · gas-phase chemistry · mass spectrometry · phosphorus transition state.…”
Section: Introductionsupporting
confidence: 90%
“…However, it was reported that in the CH 3 PO 3 H À dissociative hydrolysis, the less strained six-membered ring transition state is lower in energy than the corresponding four-membered transition state and facilitates the process. [7][8] The same influence of the water molecule was found in the [PO 3 …”
supporting
confidence: 68%
See 1 more Smart Citation
“…At low radio-frequency pulse intensity, the CAD spectrum of H 3 P 2 O 7 À ions displayed only the PO 3 À fragment ion at m/z 79, corresponding to the loss of an H 3 PO 4 molecule. If radio-frequency pulses of higher intensity were used, the abundance of the ion at m/z 79 increased and small amounts of the ion at m/z 159 were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Under low collision-energy conditions, the spectrum displayed the fragment at m/z 159, HP 2 O 6 À , corresponding to the loss of a water molecule. At slightly higher collision energies, it displayed the ion at m/z 79, PO 3 À , corresponding to the loss of H 3 PO 4 . As the collision energies were increased, this ion became the most important fragmentation channel with a relative intensity of 62.4 % at 30 eV.…”
Section: Resultsmentioning
confidence: 99%